Antifungal potential of Sphagnum moss in growing media - Tahvonen, Risto; Silvan, Niko (Suoseura, 2025)
The cinnamon mould (Peziza ostracoderma Korf) and Penicillium spp. never grow on the surface of a living Sphagnum moss media. Antifungal effect of Sphagnum moss medium also works against the major soil- and seed-borne plant fungal diseases. Good examples of the suppressive effect are seedborne Alternaria damping-off on cabbage seedlings and soil-borne Pythium root diseases on the cucumber. The disease control effect varies considerably between mires. The most effective moss batch caused almost complete protection against Pythium damping-off. The best antifungal properties were found in almost pure Sphagnum moss mixtures that had formed in the last 11, 40 and 64 years after the previous moss harvest, and the dominant species were other than the most common specie of the raised bog, Sphagnum fuscum (Schimp) H. Klinggr. When the moss was dried at the temperature of 60 or 70 °C, the antifungal effect was significantly enhanced. The seedlings remained healthy for at least two weeks, while a large proportion of the seedlings became ill in untreated moss medium. When the Sphagnum moss was kept dry, the antifungal property remained unchanged for several years. The longest measured shelf life was six years. Microbial concentrations of the mosses showed that the moss, harvested at the depth of 10–30 cm or kept dry for 4 years, was practically free of living fungi and bacteria. The moss harvested from the upper 0–10 cm layer of the mires contained measurable levels of Penicillium spp. and bacteria, but concentrations were only a fraction of those found in Sphagnum peat. When oatmeal was added to the strongly suppressive moss, the disease suppression effect of the moss was completely lost. In the moss samples, which naturally had completely inhibited the activity of Pythium disease for two weeks, the P. ultimum, Trow fungus, was fully alive, when the moss sample was transferred to rich nutrient potato dextrose agar (PDA). Based on microbial assays and heat treatment tests, the antimicrobial property of the Sphagnum moss is based almost exclusively on chemicals produced by living moss itself and the mode of action on fungal diseases is antifungal.
Keywords: Alternaria brassicicola; Penicillium spp.; Peziza ostracoderma; Pythium ultimum; Sphagnum moss harvesting